Bad girl and unmet family planning need among Sub-Saharan African adolescents: the role of sexual and reproductive health stigma - Kelli Stidham Hall; Abubakar Manu; Emmanuel Morhe; Vanessa K. Dalton; Sneha Challa; Dana Loll; Jessica L. Dozier; Melissa K. Zochowski; Andrew Boakye; Lisa H. Harris (Qualitative Research in Medicine & Healthcare)
Adolescent pregnancy contributes to high maternal mortality rates in Sub-Saharan Africa. We explored stigma surrounding adolescent sexual and reproductive health (SRH) and its impact on young Ghanaian women’s family planning (FP) outcomes. We conducted in-depth, semi-structured interviews with 63 women ages 15-24 recruited from health facilities and schools in Accra and Kumasi, Ghana. Purposive sampling provided diversity in reproductive/relationship/socioeconomic/religious characteristics. Using both deductive and inductive approaches, our thematic analysis applied principles of grounded theory. Participants described adolescent SRH experiences as cutting across five stigma domains. First, community norms identified non-marital sex and its consequences (pregnancy, childbearing, abortion, sexually transmitted infections) as immoral, disrespectful, and disobedient, resulting in bad girl labeling. Second, enacted stigma entailed gossip, marginalization, and mistreatment from all community members, especially healthcare workers. Third, young sexually active, pregnant, and childbearing women experienced internalized stigma as disgrace, shame and shyness. Fourth, non-disclosure and secret-keeping were used to avoid/reduce stigma. Fifth, stigma resilience was achieved through social support. Collectively, SRH stigma precluded adolescents’ use of FP methods and services. Our resulting conceptual model of adolescent SRH stigma can guide health service, public health, and policy efforts to address unmet FP need and de-stigmatize SRH for young women worldwide.